2021
DOI: 10.55563/clinexprheumatol/h9tc57
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis-associated interstitial lung disease: epidemiology, risk/prognostic factors, and treatment landscape

Abstract: Objective. To summarise the epidemiology, risk and prognostic factors, and treatment landscape of rheumatoid arthritis-associated interstitial lung disease (RA-ILD). Methods. Targeted and systematic literature reviews were conducted to characterise the epidemiology and treatment landscape associated with RA-ILD, respectively. MEDLINE®, Embase, and CENTRAL were searched via OvidSP in March 2019 and December 2018. The results were narratively summarised.Results. A total of 24 and 20 publications were captured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
0
20
1
1
Order By: Relevance
“…A systemic review showed the prevalence of RA-ILD ranged from 1.8% to 67% (median: 24.9%). 4 The incidence of RA-ILD in Taiwan’s nationwide population-based cohort study was 0.7%, with an incidence rate ratio (IRR) of 9.05. 5 A recent meta-analysis by Qiu et al 6 has shown 10 factors associated with increased risk of mortality in RA-ILD: older age, male sex, smoking history, lower diffusing capacity of the lung for carbon monoxide, lower forced vital capacity predicted, higher composite physiological index, usual interstitial pneumonia (UIP) pattern on high-resolution CT, emphysema presence and acute exacerbation of ILD.…”
Section: Introductionmentioning
confidence: 99%
“…A systemic review showed the prevalence of RA-ILD ranged from 1.8% to 67% (median: 24.9%). 4 The incidence of RA-ILD in Taiwan’s nationwide population-based cohort study was 0.7%, with an incidence rate ratio (IRR) of 9.05. 5 A recent meta-analysis by Qiu et al 6 has shown 10 factors associated with increased risk of mortality in RA-ILD: older age, male sex, smoking history, lower diffusing capacity of the lung for carbon monoxide, lower forced vital capacity predicted, higher composite physiological index, usual interstitial pneumonia (UIP) pattern on high-resolution CT, emphysema presence and acute exacerbation of ILD.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary involvement in RA has been the subject of increasing interest in recent years, particularly interstitial lung disease (ILD) as one of the most severe extra-articular manifestation, leading to progressive respiratory failure (Salaffi et al 2019). ILD occurs in 1.8% to 67% of RA patients, determining a worse prognosis and mortality (Fazeli et al 2021;Spagnolo et al 2018;Raimundo et al 2019). The management and treatment of RA-ILD are challenging because there is still little information available and there are no clinical trials dedicated on the topic, although this aspect is increasingly considered by guidelines (Holroyd et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is underestimated because it is often paucisymptomatic [ 26 ]. Early recognition of lung involvement might reduce the progression to lung fibrosis and be associated with and early introduction of a bDMARD or an optimal therapeutic regimen limiting some csDMARDs as leflunomide that could be detrimental for lung involvement [ 27 ]. In our cohort ILD has a prevalence of 18% and seems to be associated with a worse prognosis in terms of csDMARDs multiple failure, although this data was not confirmed in the multivariable analysis possible reflecting the heterogeneity of enrolled patients in a real-life retrospective cohort.…”
Section: Discussionmentioning
confidence: 99%